COMPARATIVE EFFECT OF ENVIROMENTAL EXPOSURE ON THE QUALITY CONTROL ASSESSMENT OF CIPROFLOXACIN TABLET MARKETED IN GOMBE SOUTH, NIGERIA - Usman M.A.; Auwal S.; Zezi A.U; Ya‟u J.; Buba, I. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
In Nigeria, ciprofloxacin is commonly prescribed in the treatment of infectious diseases. Massive importation with poor market regulations has allowed the product to be handled by non-professionals. This has led to poor storage and the drug being exposed to adverse environmental factors like; heat, light, moisture thereby causing deterioration of the product. The quality assessment test for environmentally exposed ciprofloxacin was compared with non-exposed tablet. The tests carried out were; Identification, assay, disintegration, friability and dissolution. From the results obtained, both the exposed and non-exposed responded positively to chloride test according to B.P 2002 specification, confirming the presence of ciprofloxacin hydrochloride. The percentage (%) content (assay) of the exposed and the non-exposed were 82.9 and 98.3 respectively (the acceptable range is 95-105%). The disintegration and friability tests for both the exposed and non-exposed were within the established specification of ≤30 min (for film coated tablet) and ≤ 1% respectively. The values obtained were 4.21 and 2.94 min for disintegration, and 0.16 and 0.00% for friability test respectively for the exposed and non-exposed. The percentage released for the exposed and non-exposed tablets were 66.0 and 98.0 respectively (the acceptable limit is ≥ 70%). In conclusion, exposure of ciprofloxacin to unfavorable condition such as sunlight, humidity, moisture and poor storage condition of Gombe South town (Billiri) lead to decrease in percentage content and percentage drug release of ciprofloxacin hydrochloride in the tablet sample indicating eventual low quality tablet.